Public infrastructures, public consumption and welfare in a new open economy macro model - Giovanni Ganelli; Juha Tervala (Bank of Finland, 2009)
This paper focuses on the trade-off faced by governments in deciding the allocation of public expenditures between productivity-enhancing public infrastructures and utility-enhancing public consumption in a two-country model. The results show that a permanent increase in the domestic stock of public capital financed by a reduction in public consumption raises domestic welfare if the productivity of public capital is high and the weight of public consumption in private utility is low compared with private consumption. The effect on foreign welfare is negative in the short run, but positive in the long run. This implies that, if foreign authorities care not only about the present discounted value of welfare but also about welfare dynamics, a permanent domestic reallocation of public spending might result in a virtuous global technological cycle.
URN:NBN:fi:bof-20140807545
Keywords: E62; F41; H42; H54; 330; public spending composition; welfare; imperfect competition; nominal rigidities